Research on the Influence of Wheel Polygonization on Axle Stress. (7th April 2021) - Zhang, Fubing; Wang, Qunsheng; Zhang, Zhengqiao; Zhu, Bin; Yang, Zhenhuan
Abstract : To study the influence of wheel polygonization on the dynamic stress of the wheel axle, a vehicle-track rigid-flexible coupling dynamic model was established. In the model, the wheelset, axle box, and track system were modelled as flexible bodies to consider the influence of elastic vibration. At the same time, the dynamic stress on key positions of the axle under the wheel polygonization excitation was measured on the high-frequency vibration test rig. The accuracy of the model was verified by comparison with the test results. The wheel axle stress under the excitation of the wheel polygonization with different orders, wave depths, and running speed was calculated. The results show that the wheel polygonization can increase the amplitude of the axle dynamic stress, and the larger the wave depth of the wheel polygonization, the larger the stress amplitude. When the wheel polygonization frequency is close to the frequency of the wheelset elastic vibration mode, the wheelset first-order bending and second-order bending modes have a great influence on the axle stress. The resonance vibration of the wheelset elastic modal can cause the dynamic stress on key positions of the axle increase sharply.